Examining the Effects of Mirror Therapy on Psychological Readiness and Perception of Pain in ACL-Injured Female Football Players - Tiziana D’Isanto; Francesca D’Elia; Giovanni Esposito; Gaetano Altavilla; Gaetano Raiola (Journal of Functional Morphology and Kinesiology, 2022)
Virtual reality-guided imagery (VRGI) and mirror therapy (MT) have been used in isolation to treat patients suffering from different injuries. However, no attempts have been made to understand the effects of combined VRGI and MT added to conventional physical therapy, and no information exists regarding perceptual responses to these rehabilitation strategies in female football players. Thus, this study aimed to examine the effect of MT added to conventional rehabilitation on psychological readiness and perception of pain in ACL-injured female football players. Thirty ACL-injured female football players competing in the 2nd and 3rd Italian tier who underwent an ACL rehabilitation program from the same clinic participated in this study. Players were randomly distributed in an MT group (n = 15) and a CON group (n = 15). All participants reported their perception of pain on a VAS before and after the interventions and their psychological readiness to return to sport after ACL injury and reconstruction surgery on the ACL-RSI scale after the intervention. An independent-sample t-test was performed to assess between-group differences in post-intervention ACL-RSI, and a further independent-sample t-test to assume non-significant differences between VAS values before the intervention. A two-way repeated-measures analysis of variance was used to test the null hypothesis of no different change in VAS over time between groups. After the intervention, the MT group perceived largely greater psychological readiness (p < 0.01). MT and CON groups experienced a large reduction in VAS after the intervention (p < 0.001). However, a small time × group interaction was observed (p = 0.023). MT reported a greater perception of the psychological readiness of the soccer players and a lower perception of pain than those who performed conventional therapy.